2020
DOI: 10.1039/c9fo02425e
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of protective effects between two sea cucumber hydrolysates against diet induced hyperuricemia and renal inflammation in mice

Abstract: Differences in the anti-hyperuricemic and anti-inflammation effects between two sea cucumber hydrolysates in diet induced hyperuricemic mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 49 publications
6
77
2
1
Order By: Relevance
“…Edible protein-derived oligopeptides are attractive candidates owing to their beneficial effects on hyperuricemia and their safety in rodent models. [20,21] In the present study, AJOP, with known composition, was prepared from A. japonicus (Table S2, Supporting Information) [7] ). We found that a relatively low dose of AJOP significantly alleviated hyperuricemia, renal injury, and systemic inflammation, without evident side effects (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Edible protein-derived oligopeptides are attractive candidates owing to their beneficial effects on hyperuricemia and their safety in rodent models. [20,21] In the present study, AJOP, with known composition, was prepared from A. japonicus (Table S2, Supporting Information) [7] ). We found that a relatively low dose of AJOP significantly alleviated hyperuricemia, renal injury, and systemic inflammation, without evident side effects (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…[11] In our previous study on the anti-hyperuricemic effects of AJOP, the fecal microbiota was analyzed, and differences among the control, model, and treatment groups were observed. [7] However, different environmental factors and functions of GIT segments lead to different microbiota profiles. [12,13] The limited measurement of fecal microbiota cannot provide comprehensive information on the changes in the microbiota during AJOP treatment and is not sufficient to clarify the anti-hyperuricemic effects of AJOP on microbiota modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Following that, the mice are given isoflurane anesthesia, blood samples are collected from the eyelids, and serum is isolated by centrifugation for 15 min at 4 °C and 3000 rpm, and then stored at 80 °C for biochemical studies. The mice are sacrificed through cervical dislocation after sample processing, and their visceral organs are excised, weighed, and preserved at 80 °C before further study [ 41 ].…”
Section: Experimental In-vivo Models For Goutmentioning
confidence: 99%
“…Enzymatic hydrolysates of A. japonicus (EH‐JAP) and A. leucoprocta (EH‐LEU) could also inhibit the uric acid biosynthesis and promote uric acid excretion. These hydrolysates could downregulate the transcription of pro‐inflammatory cytokines, upregulate the transcription of anti‐inflammatory cytokines, and inhibit the activation of the Toll‐like receptor 4/myeloid differentiation factor 88/NF‐κB signaling pathway in a diet‐induced hyperuricemia mouse model (H. Wan et al., 2020). Kidney bean ( Phaseolus vulgaris L .)…”
Section: Introductionmentioning
confidence: 99%